Exploring the Role of Digital Literacy as a Predictor of Self-Regulated Learning in Physics Education - Riswanto, Riswanto; Hidayatullah Alarifin, Dedy; Hidayat, Arif (Jurnal Pendidikan Fisika, 2025)
The rapid integration of digital technologies into education highlights the critical importance of digital literacy in developing self-regulated learning (SRL), particularly among physics education students. This study aims to investigate the influence of digital literacy on SRL by (1) assessing the digital literacy levels of physics students, (2) examining their SRL profiles, (3) analyzing the predictive power of digital literacy on SRL, and (4) identifying which digital literacy indicators significantly impact different SRL dimensions. A quantitative, cross-sectional approach was employed with 28 undergraduate students using validated instruments: the Digital Literacy Scale and the Online Self-Regulated Learning Questionnaire. The results revealed high digital literacy levels, especially in media utilization (M = 4.17), but lower performance in evaluating digital information (M = 3.96). SRL was strongest in planning (M = 3.3) and monitoring-evaluation (M = 3.2), while autonomy (M = 2.5) and motivation-discipline (M = 2.8) were less developed. Regression analyses confirmed digital literacy as a significant predictor of SRL (β = 0.50; p = 0.016), explaining 58.9% of the variance. Among the digital literacy indicators, digital technology skills emerged as the most influential factor across all SRL dimensions. Furthermore, gender was found to moderate the relationship, with a stronger effect observed in female students. This study contributes to physics education by demonstrating the importance of integrating digital literacy training, particularly in technology skills and information evaluation, into curriculum design to support students' independent learning capabilities in digital learning environments.